Sotvori dobro . Sotvori dobro . Do Good . Сотвори добро - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A charity program for disabled children and teenagers; the Sergiev-Posad school for blind, deaf and dumb children; building cooperatives involved in charity; a guest house for elderly people in Moscow. Contributors: Petrovskaia, Irina (Anchor) Благотворительная программа для детей и подростков-инвалидов; Сергиев-Посадский детский дом для слепоглухонемых детей; строительные кооперативы, вовлеченные в благотворительную деятельность; пансионат для пожилых людей в Москве. Создатели: Петровская, Ирина (Ведущий/Ведущая)